Komite Audit Sebagai Pemoderasi Pengaruh Workload dan Masa Perikatan Audit Pada Kualitas Audite - Rusli, Theresia Julina; Wiratmaja, I Dewa Nyoman (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 11 No 1 (2016)DO - 10.24843/JIAB.2016.v11.i01.p06, 2016)
This  research  aims to find empirical evidence  about the impact  of  workload  and  audit tenure  on  audit quality  and  using audit  committee  as  a  moderating  variable. This  research  focused  on  manufacturing companies  that  listed  on  the  Indonesia Stock Exchange. Sample was collected using   purposive sampling method and resulted 31  companies as a final sample.  The  data are analyzed by using Moderated Regression Analysis (MRA). The results of  this research indicate  that the  workload  has a negative  impact on  audit quality.  Audit tenure has a positive impact on audit quality. Audit committee reduces the negative impact of workload on audit quality. And audit committee reduces the positive impact of audit tenure on audit quality. Keywords: Workload, audit tenure, audit committee, audit quality
Keywords: Workload, Audit Tenure, Audit Committee, Audit Quality